MANAGING EMOTIONS ON THE JOB AND AT HOME: UNDERSTANDING THE CONSEQUENCES OF MULTIPLE EMOTIONAL ROLES - Wharton, Amy; Erickson, Rebecca I. (Academy of Management Review, 1993)
Amy S. Wharton, Rebecca J. Erickson, Managing Emotions on the Job and at Home: Understanding the Consequences of Multiple Emotional Roles, The Academy of Management Review, Vol. 18, No. 3 (Jul., 1993), pp. 457-486